(untitled) (Research, Society and Development, 2022)
The objective of the work was to relate the nutritional status of olive orchards from the central region of the Rio Grande do Sul with fruit yield and identify unadjusted points in the fertilization recommendation system to be improved. Soil, leaf, and fruit samples were taken from eight orchards, between 2018 and 2020, and were evaluated for the contents of N, P, K, B, pH, TOC, Al+3, and soil texture. The 20-40 cm layer in soil showed acidity and Al+3 content at potentially restrictive levels. The available P and B contents in soil were considered low. In leaf tissue, K and N presented high contents. The correlations revealed that fruit yield was limited by high N contents on leaves, especially in winter. B content in fruits diminished in higher soil pH, suggesting that the B threshold value in soil for olives in the south of Brazil should be pH-dependent.